Neurocognitive outcome in children with sickle cell disease after myeloimmunoablative conditioning and haploidentical hematopoietic stem cell transplantation: a non-randomized clinical trial - Braniecki, Suzanne; Vichinsky, Elliott; Walters, Mark C.; Shenoy, Shalini; Shi, Qiuhu; Moore, Theodore B.; Talano, Julie-An; Parsons, Susan K.; Flower, Allyson; Panarella, Anne; Fabricatore, Sandra; Morris, Erin; et al. (Frontiers in Neurology, 2024)
Background: Due to risk of cerebral vascular injury, children and adolescents with high-risk sickle cell disease (SCD) experience neurocognitive decline over time. Haploidentical stem cell transplantation (HISCT) from human leukocyte antigen matched sibling donors may slow or stop progression of neurocognitive changes. Objectives: To determine if HISCT can ameliorate SCD associated neurocognitive changes and prevent neurocognitive progression, determine which specific areas of neurocognitive functioning are particularly vulnerable to SCD, and determine if there are age related differences in neurocognitive functioning over time Methods: We performed neurocognitive and neuroimaging in SCD recipients following HISCT. Children and adolescents with high-risk SCD who received parental HISCT utilizing CD34 + enrichment and mononuclear cell (T-cell) addback following myeloimmunoablative conditioning received cognitive evaluations and neuroimaging at three time points: pre-transplant, one-year, and two years post-transplant. Results: Nineteen participants (13.1 ± 1.2 years [3.3-20.0]) received HISCT. At two years posttransplant, neuroimaging and cognitive function were stable. Regarding age-related differences pre-transplantation, older children (≥13 years) had already experienced significant decreases in language functioning (p < 0.023), verbal intelligence quotient (p < 0.05), nonverbal intelligence quotient (p < 0.006) and processing speed (p < 0.05), but normalized post-HISCT in all categories. Conclusions: Thus, HISCT has the potential to ameliorate SCD associated neurocognitive changes and prevent neurocognitive progression. Further studies are required to determine if neurocognitive performance remains stable beyond two years post-HISCT. Clinical Trial Registration: The study was conducted under an investigator IND (14359) (MSC) and registered at clinicaltrials.gov (NCT01461837).